2023
DOI: 10.1161/circinterventions.122.012700
|View full text |Cite
|
Sign up to set email alerts
|

Deferred Versus Performed Revascularization for Left Main Coronary Disease With Hemodynamic Significance

Abstract: Background: The majority of randomized controlled trials of revascularization decision-making excludes left main coronary artery disease (LMD). Therefore, contemporary clinical outcomes of patients with stable coronary artery disease and LMD with proven ischemia remain poorly understood. The aim of this study was to assess the long-term clinical outcomes of physiologically significant LMD according to the treatment strategies of revascularization versus revascularization deferral. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…In conclusion, this novel work by Warisawa et al 9 is the first contemporary study describing the natural history of stable, angiographically intermediate, hemodynamically significant LMD and strongly supports revascularization with either precision PCI or coronary artery bypass grafting with left internal mammary artery to left anterior descending artery grafting over deferral to achieve an early and sustained mortality benefit. Although a randomized controlled trial is the gold standard to drive evidence-based clinical decision-making, the findings from this observational study are compelling and robust enough to dispel any remaining clinical equipoise regarding an initial strategy of deferral versus revascularization for hemodynamically significant LMD and obviate the need for a confirmatory randomized controlled trial.…”
Section: See Article By Warisawa Et Alsupporting
confidence: 53%
See 1 more Smart Citation
“…In conclusion, this novel work by Warisawa et al 9 is the first contemporary study describing the natural history of stable, angiographically intermediate, hemodynamically significant LMD and strongly supports revascularization with either precision PCI or coronary artery bypass grafting with left internal mammary artery to left anterior descending artery grafting over deferral to achieve an early and sustained mortality benefit. Although a randomized controlled trial is the gold standard to drive evidence-based clinical decision-making, the findings from this observational study are compelling and robust enough to dispel any remaining clinical equipoise regarding an initial strategy of deferral versus revascularization for hemodynamically significant LMD and obviate the need for a confirmatory randomized controlled trial.…”
Section: See Article By Warisawa Et Alsupporting
confidence: 53%
“…In the current issue of Circulation: Cardiovascular Interventions, Warisawa et al 9 report propensity-matched data from an international multicenter registry of patients with stable, hemodynamically significant LMD (instantaneous wave-free ratio ≤0.89). The investigators compared outcomes between 148 total patients-74 who underwent revascularization (56% PCI and 44% coronary artery bypass grafting) and 74 in whom revascularization was deferred.…”
Section: See Article By Warisawa Et Almentioning
confidence: 99%
“…Once revascularization has been performed, however, in the LM-revascularization group of this study, baseline iFR LM and FFR LM values were not found to be predictors of MACE, as has been previously reported [ 21 , 22 ]. This may suggest that the more important drivers of clinical outcomes in LM-revascularization are the judicious use of intracoronary physiology and imaging in PCI, and the routine use of internal mammary artery grafting during CABG [ 3 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ealy reports from decades ago demonstrated an extremely poor prognosis in patients with LMD treated with medical therapy alone, showing a 5 year survival of less than 50% [ 1 , 2 ]. Despite advances in the contemporary medical therapy of stable coronary artery disease (CAD), a prognosis in patients with physiologically significant LMD is recently reported to still remain suboptimal with rates of adverse cardiovascular events of approximately 30% at 4 years [ 3 ]. Considering such a high-risk disease entity, diagnostic guidelines recommend ruling out LMD as a first step of stable CAD [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical utility would be emphasized validly if a randomized controlled trial demonstrated noninferior or superior outcomes in patients who undergo revascularization with imaging-based FFR compared with those with wire-based FFR, especially in the subset of complex coronary lesions, although improvement of clinical outcomes in percutaneous coronary intervention has been demonstrated under the guidance of imaging-based FFR compared with conventional angiography guidance until today. 3 Forth, the clinical applicability for the left main disease, which is one of the most complex coronary lesions and potentially life-threatening disease entity even in contemporary practice, 10 was not assessed in the current analysis and data for this subset are limited. 11 Finally, it still remains debatable whether the accuracy of imaging-based FFR is satisfactory or not in predicting post-percutaneous coronary intervention physiological outcomes, which is also of great interest in this field.…”
Section: See Article By Wu Et Almentioning
confidence: 99%